2018
DOI: 10.1038/s41598-018-33993-9
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA amplicon sequencing reveals a polymicrobial nature of complicated claw horn disruption lesions and interdigital phlegmon in dairy cattle

Abstract: Lameness represents an intractable problem for the dairy industry. Complicated claw horn disruption lesions, interdigital hyperplasia, and interdigital phlegmon are important lameness causing foot lesions. Their aetiology is multifactorial, but infectious processes are likely implicated in disease pathogenesis. Our aim was to investigate the bacterial profiles of these lesions using 16S rRNA gene sequencing of samples obtained from 51 cattle across ten farms in the UK. In this study, interdigital hyperplasia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 60 publications
(54 reference statements)
3
30
0
Order By: Relevance
“…Most of these bacterial families were also present at relatively high abundances in interdigital skin samples from the healthy feet of dairy cattle or slurry samples from the dairy herd environment [13,15]. Moreover, in this study, Clostridiales Family XI was detected at significantly higher relative abundance in CF samples compared with SB and CB samples, and it was formerly found to be more abundant in skin lesions compared to healthy skin samples of cattle claws [2]. Our results also showed that the relative abundances of genera Solibacillus and Clostridium sensu stricto 1 from the same phylum Firmicutes were significantly higher in CF samples than in other groups, those two genera were reported to be associated with gastrointestinal disease in human and cows [20,28].…”
Section: Thesupporting
confidence: 49%
See 1 more Smart Citation
“…Most of these bacterial families were also present at relatively high abundances in interdigital skin samples from the healthy feet of dairy cattle or slurry samples from the dairy herd environment [13,15]. Moreover, in this study, Clostridiales Family XI was detected at significantly higher relative abundance in CF samples compared with SB and CB samples, and it was formerly found to be more abundant in skin lesions compared to healthy skin samples of cattle claws [2]. Our results also showed that the relative abundances of genera Solibacillus and Clostridium sensu stricto 1 from the same phylum Firmicutes were significantly higher in CF samples than in other groups, those two genera were reported to be associated with gastrointestinal disease in human and cows [20,28].…”
Section: Thesupporting
confidence: 49%
“…Lameness is one of the most common diseases in the dairy industry that result in increased culling rate and economic losses [1]. The methods for diagnosis and therapy in lameness have greatly improved [2,3]. However, it is also critical to develop preventive measures of lameness in indoor housing systems.…”
Section: Introductionmentioning
confidence: 99%
“…There is paucity of data on the association between CT and wall fissures and scissors claws, but there are few reports on HYP and CSC. Schulz et al [47] reported that corrective CT resulted in lower prevalence of HYP during a 41 week trial, while the concurrent presence of DD and HYP in lactating cows during hoof examination was suggestive of positive association between the two lesions [64]. Infectious process has been implicated in the pathogenesis of HYP [64], but there is no current information on how corrective or preventive CT for DD or other infectious claw lesions might influence the levels of HYP.…”
Section: Other Claw Lesionsmentioning
confidence: 99%
“…Schulz et al [47] reported that corrective CT resulted in lower prevalence of HYP during a 41 week trial, while the concurrent presence of DD and HYP in lactating cows during hoof examination was suggestive of positive association between the two lesions [64]. Infectious process has been implicated in the pathogenesis of HYP [64], but there is no current information on how corrective or preventive CT for DD or other infectious claw lesions might influence the levels of HYP. On the other hand, CSC is characterized by an inward curvature of the abaxial wall and can be managed by corrective CT [65].…”
Section: Other Claw Lesionsmentioning
confidence: 99%
“…Consideration should also be given to other aspects of hygiene during foot-trimming, particularly cleanliness of gloves, since it has been shown that treponemes can survive on gloves for up to 3 days after handling sheep feet showing the analogous disease, contagious ovine digital dermatitis [24]. The use of disinfectants on trimming tools will not only assist in controlling transmission of treponemes between animals and farms but will also have the effect of reducing transmission of other microbes which are known to contribute to digital dermatitis and other important foot lesions [33].…”
Section: Discussionmentioning
confidence: 99%